2008
DOI: 10.1038/nature07233
|View full text |Cite
|
Sign up to set email alerts
|

Replication fork movement sets chromatin loop size and origin choice in mammalian cells

Abstract: Genome stability requires one, and only one, DNA duplication at each S phase. The mechanisms preventing origin firing on newly replicated DNA are well documented, but much less is known about the mechanisms controlling the spacing of initiation events(2,3), namely the completion of DNA replication. Here we show that origin use in Chinese hamster cells depends on both the movement of the replication forks and the organization of chromatin loops. We found that slowing the replication speed triggers the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
203
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(228 citation statements)
references
References 26 publications
18
203
0
Order By: Relevance
“…Interestingly, fork speed was significantly higher and S-phase length was shorter in two ICF cell lines out of three. Changes in replication fork speed may be associated with changes of inter-origin distances; 22,23 however, this did not occur in ICF cell lines that had inter-origin distances comparable to controls. A DNA replication defect generalized to the whole genome was unexpected considering that major epigenetic changes in ICF patients occur in heterochromatic regions (reviewed by Ehrlich et al 26 ) and that the shift of replication timing is restricted to heterochromatic regions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, fork speed was significantly higher and S-phase length was shorter in two ICF cell lines out of three. Changes in replication fork speed may be associated with changes of inter-origin distances; 22,23 however, this did not occur in ICF cell lines that had inter-origin distances comparable to controls. A DNA replication defect generalized to the whole genome was unexpected considering that major epigenetic changes in ICF patients occur in heterochromatic regions (reviewed by Ehrlich et al 26 ) and that the shift of replication timing is restricted to heterochromatic regions.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in replication fork speed may be associated with compensatory changes of inter-origin distances. 22,23 To check whether the increase in fork speed in ICF3 and ICF4 was associated with a change of the inter-origin distance, we measured the center-to-center distance between two adjacent CldU tracks (inter-track distance). This measurement is currently used to estimate inter-origin distance.…”
Section: Global Replication Fork Speed Was Increased In Icf Cellsmentioning
confidence: 99%
“…This result could be due to selection pressures inherent to generating fibroblast clones harboring CNVs in these regions or, alternatively, a more complex relationship between fragile site instability and CNVs secondary to their common induction by replication stress. Both depletion of nucleotide pools by HU and polymerase inhibition by APH lead to reduced replication fork rate, fork stalling, and activation of dormant origins (51)(52)(53)(54). It has recently been shown that dormant origins are only activated in early replicating regions, whereas origin firing is suppressed by S-phase checkpoints in late-replicating regions of the genome (54).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular combing of single DNA molecules demonstrated that Chk1 depletion resulted in a clear reduction in origin spacing (∼40% of control cells) as well as in the rate of fork elongation throughout the labeling period. However, since slowing the replication speed very rapidly triggers the recruitment of latent origins (Courbet et al 2008), it is not clear at this stage whether Chk1 regulates either or both activation of origins or fork velocity. Molecular combing also revealed that loss of Chk1 frequently stalls and collapses active forks.…”
Section: Chk1 But Not Chk2 Is a Regulator Of The Origin Firing Programentioning
confidence: 99%